First report of Neotherium mandible from the Miocene Shimane, Japan: Review of basal odobenids in the western North Pacific. (2nd January 2022) - Tonomori, Wataru; Kawano, Shigenori; Irizuki, Toshiaki
ABSTRACT: The present study describes a new specimen of a pinniped mandible from the lower Miocene Irino Sandstone Member of the Takami Formation (approximately 16.5 Ma), Shimane, western Japan, as a basal odobenid Neotherium mirum Kellogg, 1931 . Our review of the basal odobenid records from Japan reveals that it is the first record of N. mirum and the western- and southernmost record in the western North Pacific. In addition, the present specimen is one of the oldest records of N. mirum around the world. The records clearly showed that Japan was one of the major habitats for the basal odobenids. The early evolution of odobenids occurred around the North Pacific; however, there is no record of basal odobenids with a trans-Pacific distribution. Our study demonstrates that N. mirum was widely distributed in the North Pacific, and suggests that the basal odobenids already had the mobility to expand their distribution.